The Effect Of Tactical Learning In Competitive Dual On The Development of Motor Speed Response Of A Random Stimuli And Sabre Fencer’s Achievement - Abedullah, Alaa (Journal of Physical Education, 2016)
The aim of the study was to identify the impact Of Tactical Learning in competitive Fencing on development of motor response speed of a Random stimulus And Sabre Fencer’s Achievement. The researcher sued the experimental method on a subjects consisting of ten foil fencers ages (15 – 17). The subjects were divided into two groups. The main conclusion is that tactical learning affects the development of motor response speed of a random stimuli and the level of Fencer Achievement. The researcher recommended the use of Tactical Learning during competitive duals. Keywords: Sabre Fencing, Speed of Motor Response, Tactical Learning, Achievement